2008
DOI: 10.1111/j.1365-2621.2008.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical and sensory attributes in conjunction with multivariate analysis of two potato (Solanum tuberosum L.) cultivars after 90 days of storage: an exploratory authentication study

Abstract: Original articlePhysico-chemical and sensory attributes in conjunction with multivariate analysis of two potato (Solanum tuberosum L.) cultivars after 90 days of storage: an exploratory authentication study Summary Two cultivars of potato (Spunta and Agria), were studied in terms of their physico-chemical and sensory characteristics. These cultivars were cultivated in three geographical regions of Greece (Macedonia, North Greece; Thessaly, Central Greece; Peloponnese, South Greece) and were stored for 90 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In this study, although the pH in the extract solution from cortex tissue ranged from 5.9 to 6.3, the tendency of a smaller starch content at higher pH might support the possibility that cortex pH affects indirectly starch degradation via enzymatic activation of phosphorylase in higher pH condition. The acidity of tuber originated from endogenous citric acid in the experiment using two different cultivars, Agria and Spunta (Arvanitoyannis et al 2008), but the difference in pH of extract solution in this study was not clear.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In this study, although the pH in the extract solution from cortex tissue ranged from 5.9 to 6.3, the tendency of a smaller starch content at higher pH might support the possibility that cortex pH affects indirectly starch degradation via enzymatic activation of phosphorylase in higher pH condition. The acidity of tuber originated from endogenous citric acid in the experiment using two different cultivars, Agria and Spunta (Arvanitoyannis et al 2008), but the difference in pH of extract solution in this study was not clear.…”
Section: Discussionmentioning
confidence: 61%
“…The quality of composition and morphological traits drastically change by the heat of cooking. And the flavor of long-term stored potato tubers was different from the flavor of fresh ones (Jansky 2008), the physico-chemical and sensory characteristics in potato were impacted by chilling storage (Arvanitoyannis et al 2008). However, intact traits in components and morphological form of fresh tubers must be important for potato breeding aimed at good flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the solids that are excluded from juiced samples contain significant unrecovered acidity in intact vacuoles. Similar methods of mechanical homogenization have been employed by some previous researchers (Arvanitoyannis et al 2008;Hyde and Morrison 1964;Pardo et al 2000;Nourian et al 2002).…”
Section: Sample Preparation and Typementioning
confidence: 91%
“…Increased sugars associated with low pH result in undesirable chip and fry color (Iritani and Weller 1974). Lower pH has been highly associated with overall desirable taste, apparently because evaluators favor sweet-tasting cooked potato (Jitsuyama et al 2009;Jansky 2008;Arvanitoyannis et al 2008). Pardo et al (2000) found no link between pH and flavor parameters, but the range of pH was small in that experiment.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation